Powiązania literackie Polski i Azji Centralnej: literatura polska w przekładach na łamach uzbeckiego czasopisma „Jahon adabiyoti” - Genjemuratov, Bahtiyar (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2015)
Autor omawia przykłady aktualnego stanu kulturalno-literackiej współpracy narodu polskiego i uzbeckiego. Jego zdaniem w dobie globalizacji elity twórcze czują potrzebę stałego dialogu i wzajemnych powiązań różnych państw i całego świata w ogóle, czego przykładem są stosunki między Polską i Uzbekistanem, a przejawem między innymi przekłady literatury. Autor zwraca uwagę, że przekład poezji wymaga od tłumacza dużej wiedzy ogólnej, powinien on także dysponować wiedzą w zakresie ogólnego kontekstu kulturowego.

The author discusses the examples of the current status of cultural and literary cooperation between the Polish and Uzbek nations. In his opinion, in the period of globalization, creative elites feel a need for a permanent dialogue and mutual links, between different states and on a global scale, as exemplified by Polish-Uzbekistani relations expressed in terms of translations of literature, among other things. The author emphasises that translating poetry calls for the translator’s comprehensive general knowledge, encompassing also the awareness of the general cultural context.
Literary links between Poland and Central Asia: translations of Polish literature in the Uzbekistani periodical “Jahon adabiyoti”
Keywords: Uzbekistan; polityka kulturalna; literatura polska na świecie; Uzbekistan; cultural policy; Polish literature in the world